As factors of corruption of insufficient objectivity of the system of criteria of estimation of activity of organs of internal affairs of Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The author of the article rises the problem of objective lack of evaluation ctyteria in the organs of internal affairs of the Republic Kazakhstan. It is supposed to consider it as corruptional factor and on the basis of the thourough study its practical aspects , holding an analysis of the foreign practice, to find ways and create the modern model of the activity of the organs of internal affairs in the Republic of Kazakhstan. The result of these directions is the set of the organizing-legal decisions in creating objective, effective and ergonomic system of evaluation ctyteria in the organs of internal affairs of the Republic Kazakhstan.Key words: Republic, right, system, corruption, direction, crime, activity.